Planos diretores e desenvolvimento urbano sustentável: um estudo sobre os instrumentos urbanísticos para a recuperação de mais-valias fundiárias. - Pereira, Flavia Pedrosa (2007)
Certain public investments or changes in the urban norms contribute to private property appreciation, without the owners having to make any effort for it. This research studies intervention ways to capture part of this increased value for the public sector, called land value capture tools, through which it is possible to revert the process of public investments private possession. The first part of the analysis takes into account a large context, relating the subject to the search for a sustainable urban development, within the city right, its property social function and the current Brazilian laws. It presents examples of countries where these tools are being used and mentions the Brazilian reality concerning tax policies and urban policies which are able to capture land value. Next, a case study about Maceió, a city located in the northeast of Brazil. It investigates how its master plan and urban laws have foreseen the use of such tools, trying to identify if advances have occurred in the search for a bigger land market control and as an incentive so that the property can do its social function. The adopted methodology is one of analytical work with exploratory characteristics, where selected and revised readings have been vital, tracing the origin, the development and the influence of ideas and concepts, with the hypothesis being created within the investigation process. The study showed that the land value capture tools may help in the search for a sustainable urban development, being able to contribute to the property social function. It also showed that the elaboration of new urban laws by Brazilian cities does not mean that these instruments are being, or will be, implemented.